Odpowiedzi

Najlepsza Odpowiedź!
2010-04-09T09:07:59+02:00
1)
sinα = 0,25 = 1/4
sin²α + cos²α = 1 ---> cos²α = 1 - sin²α
cos²α = 1 -(1/4)² = 16/16 - 1/16 = 15/16
cosα = √15/√16 = √15 /4
tgα = sinα / cosα = (1/4) : (√15/4) = (1/4)* (4/√15) = 1/√15 = √15/15
ctgα = 1/tgα = 15 /√15 = √15
2)
cosα = √6/4
sin²α = 1 - cos²α = 1 - (√6/4)² = 16/16 - 6/16 = 10/16
sinα = √10 / √16 = √10/4
tgα = sinα / cosα = (√10/4) : (√6/4) = (√10/4)*(4/√6) = √10/ √6 =
= √(10/6) = √(5/3)
ctgα = 1/tgα = 1/ √(5/3)= (3/5)*√(5/3)